Cichorium intybus as a Functional Food: Bioactive Compounds and Antidiabetic Potential - Amalyadi, Rezki; Karni, Ine; Aminurrahman, Aminurrahman; Septian, I Gede Nano (CV. Media Inti Teknologi, 2025)
Background of study: Cichorium intybus L., or chicory, is a nutrient-dense plant that has traditionally been used as a forage crop and vegetable. It is now gaining attention for its bioactive compounds, which have therapeutic potential, particularly for managing type 2 diabetes mellitus.Aims and scope of paper: This systematic review examines the nutritional composition and phytochemical profile of chicory, as well as its antidiabetic mechanisms, to highlight its potential role in the prevention and management of diabetes as a functional food.Methods: A systematic literature review was conducted in accordance with PRISMA guidelines. Peer-reviewed articles published between 2019 and 2022 were identified using the databases Scopus, PubMed, and Web of Science. The eligible studies focused on chicory’s bioactive compounds and their metabolic effects. Data extraction and quality appraisal were performed using a standardized CASP checklist, and thematic synthesis was applied.Result: 36 studies were included. Chicory was found to be rich in inulin, phenolic acids (e.g., chicoric acid and caffeic acid), flavonoids (e.g., luteolin and quercetin), and sesquiterpene lactones. These compounds improve insulin sensitivity, inhibit carbohydrate-digesting enzymes, regulate lipid metabolism, and protect pancreatic beta cells via antioxidant and anti-inflammatory pathways. Chicory-derived ingredients are used in prebiotic formulations, functional foods, and animal feeds.Conclusion: Chicory has significant antidiabetic potential through multiple target mechanisms. However, the current evidence is primarily preclinical with few human trials. Standardized clinical studies are needed to validate its efficacy and determine the optimal dosage and long-term safety. Due to its accessibility and versatility, chicory is a promising functional food for supporting metabolic health and sustainable nutrition.